Manajemen Konflik Dalam Peningkatan Kinerja Guru Perspektif Al-Qur’an - Cecep Supendi; Saifuddin Zuhri (Thawalib: Jurnal Kependidikan Islam, 2022)
This study aims to explain conflict management in improving the performance of teachers from the Al-Qur'an perspective. This research is in the form of qualitative with a library research approach, research sources of the Qur'an and books of interpretation of books, journals, theses, modules and articles related to the object of research. The results showed: Strategy to manage conflict: First, Lose-Lose Strategy, by avoiding conflicts and problems that arise. Win-Lose Strategy, managing conflict through competition in the Second, competing in improving performance Third, Los-Win Strategy, by succumbing to accommodate the interests of others so as not to enlarge. Fourth, Win-Win Strategy, resolve conflicts by creating settlements through conventions or mutual agreements. Strategies in improving teacher performance, namely: increasing further education, implementing regulations on discipline, training, reward and punishment, improving welfare, developing motivation.